2008
DOI: 10.1021/ja802829d
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Valent Mn Supertetrahedra and Planar Discs as Enhanced Magnetic Coolers

Abstract: The syntheses and structures of two decametallic mixed-valent Mn supertetrahedra using 2-amino-2-methyl-1,3-propanediol (ampH2), two decametallic mixed-valent Mn planar discs using 2-amino-2-methyl-1,3-propanediol (ampH2) and 2-amino-2-ethyl-1,3-propanediol (aepH2), and a tetradecametallic mixed-valent Mn planar disc using pentaerythritol (H4peol) are reported. The decametallic complexes display dominant ferromagnetic exchange and spin ground states of S = 22, and the tetradecametallic complex displays dominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
106
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(108 citation statements)
references
References 41 publications
1
106
1
Order By: Relevance
“…The first investigation of MCE in magnetic molecules indeed focused on the most investigated SMMs, namely Mn 12 and Fe 8 . [3] What could be considered side-products of the research on SMM can however be revealed as promising magnetic refrigerants.…”
mentioning
confidence: 99%
“…The first investigation of MCE in magnetic molecules indeed focused on the most investigated SMMs, namely Mn 12 and Fe 8 . [3] What could be considered side-products of the research on SMM can however be revealed as promising magnetic refrigerants.…”
mentioning
confidence: 99%
“…1 Its use through the adiabatic demagnetization process has first focused on low temperatures. [2][3][4] Different kinds of materials have attracted interest for their MCE in low temperature region (2-4 K), including simple paramagnetic salts, 4,5 molecular nanomagnets, [6][7][8][9][10][11][12] extended porous networks, 13 garnets, 14 or intermetallic alloys. 15 For a more exhaustive insight, two recent review articles dealing with coordination compounds 16 or molecule-based 17 magnetic coolers can be consulted.…”
mentioning
confidence: 99%
“…Manganese complexes are attracting considerable interest not only in the fields of bioinorganic chemistry but also for their ability to function as progenitors of novel magnetic molecular materials [1][2][3][4][5][6]. In the former area, these complexes are significant for their redox active role in some biochemical processes, current interests in the chemistry of higher oxidation-state manganese compounds draw from their utility as models for the photosynthetic water oxidation centers [7,8].…”
mentioning
confidence: 99%
“…3). From the topological view, if each [Mn(DBA) 2 Mn] ring is considered as a 4-connected node, the structure of 1 exhibits a (4,4) topology (Fig. 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation